Perfil dos pacientes vítimas de traumatismo cranioencefálico atendidos no Hospital João XXIII em julho de 2016 e identificação dos fatores que influenciaram sua mortalidade - Ana Luisa Gonçalves Magalhães (2017)
Traumatic brain injury (TBI) is considered one of the major causes of death and disability in the world, mainly in people under 45 years old. In Brazil is estimated that more than one million people live with disabilities due TBI. Although the high incidence, there are few epidemiological studies. In order to establish the epidemiological profile of the patients suffering from TBI in a large emergency center located in Belo Horizonte, Brazil, and establish the factors that influence their morbidity and mortality, data were colleted from hospital registers during one month (July, 2016). Patients sustained TBI less than 24 hours were selected. The major cause of TBI were falls. Children were very affected. The major cases were mild TBI, but in young adults there were a big number of severe TBI. Most of the patientes were men and the TBI were less severe in women. Age, alterations in the cranial computed tomography, gravity of TBI and alterations in the pupilar reflex were factors that inflenced the morbidity and mortility. The characteristics of TBI seemed to be influenced by cultural and social factors and tablish the epidemiological profile of the victims of TBI in each center is very important to improve the treatment and to develop preventives strategies